Clinicopathological features and clinical outcomes associated with TP53 and BRAFNon‐V600 mutations in cutaneous melanoma patients. Issue 8 (2nd December 2016) - Kim, Dae Won; Haydu, Lauren E.; Joon, Aron Y.; Bassett, Roland L.; Siroy, Alan E.; Tetzlaff, Michael T.; Routbort, Mark J.; Amaria, Rodabe N.; Wargo, Jennifer A.; McQuade, Jennifer L.; Kemnade, Jan; Hwu, Patrick; et al.
Abstract : BACKGROUND: BRAF V600, NRAS, TP53, and BRAF Non‐V600 are among the most common mutations detected in non‐acral cutaneous melanoma patients. Although several studies have identified clinical and pathological features associated with BRAF V600 and NRAS mutations, limited data are available regarding the correlates and significance of TP53 and BRAF Non‐V600 mutations. METHODS: This study analyzed the patient demographics, primary tumor features, and clinical outcomes of a large cohort of non‐acral cutaneous melanoma patients who had undergone clinically indicated molecular testing (n = 926). RESULTS: The prevalence of BRAF V600, NRAS, TP53, and BRAF Non‐V600 mutations was 43%, 21%, 19%, and 7%, respectively. The presence of a TP53 mutation was associated with older age ( P  = .019), a head and neck primary tumor site ( P  = .0001), and longer overall survival (OS) from the diagnosis of stage IV disease in univariate ( P  = .039) and multivariate analyses ( P  = .015). BRAF Non‐V600 mutations were associated with older age ( P  = .005) but not with primary tumor features or OS from stage IV. Neither TP53 nor BRAF Non‐V600 mutations correlated significantly with OS with frontline ipilimumab treatment, and the TP53 status was not significantly associated with outcomes with frontline BRAF inhibitor therapy. Eleven patients with BRAF Non‐V600 mutations were treated with a BRAF inhibitor. Three patients were not evaluable for a response because of treatment cessation for toxicities; the remaining patients had disease progression as the best response to therapy. CONCLUSIONS: These results add to the understanding of the clinical features associated with TP53 and BRAF Non‐V600 mutations in advanced cutaneous melanoma patients, and they support the rationale for evaluating the prognostic significance of TP53 in other cohorts of melanoma patients. Cancer 2017;123:1372–1381. © 2016 American Cancer Society . Abstract : Although TP53 and BRAF Non‐V600 mutations are common oncogenic mutations in non‐acral cutaneous melanoma, very little is known about their clinical and pathological significance. This analysis of a large cohort of patients with advanced melanoma suggests that TP53 mutations are associated with improved outcomes in patients with advanced non‐acral cutaneous melanoma. This is a surprising finding that warrants further evaluation in this disease.